A high-energy-density quasi-solid-state carbon nanotube electrochemical double-layer capacitor with ionogel electrolyte. (13th March 2015) - Membreno, Daniel; Smith, Leland; Shin, Kyeong-Sik; Chui, Chi On; Dunn, Bruce
Abstract: This paper reports the fabrication of an electric double-layer supercapacitor that incorporates carbon nanotube electrodes with an ionogel electrolyte based on the sol–gel encapsulation of the ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate. The quasi-solid nature of the ionogel electrolyte enables this supercapacitor to become a solid-state device, which overcomes the limitations of many high-performance supercapacitors, whose liquid-based electrolyte prohibits the realization of truly compact energy storage that is practical for various existing and emerging portable electronics. The device reported here combines the intrinsic high power of an electrochemical double-layer capacitor with the increased energy density associated with the wide voltage window of the ionogel. The device was characterized by a suite of electrochemistry techniques and demonstrated both high power and high energy density.